On the back of an Asian elephant (Elephas maximus) – the backside of the elephant tourism with focus on welfare - Turesson, Veronica (2014)
Thailand had well over 26 million international visitors in 2013 and the demand after elephant-related activities are on many people's to do list when visiting Thailand.